“Navigating the Different Spaces”: Experiences of Inclusion and Isolation Among Racially Minoritized Faculty in Canada - Spafford, Marlee M.; Nygaard, Vicki L.; Gregor, Fran; Boyd, Marcia A. (Canadian Journal of Higher Education, 2006)
The intersection of multiple identities (e.g., racialization, gender, class) strongly determines an individual’s social location. In-depth interviews with 42 racially minoritized academics in Canadian universities allowed U.S. to begin to grasp the challenges faced by those who must negotiate the different spaces in an academy that is predominately white, Eurocentric and male. Using an anti-racist framework, we found that the level of inclusion that racially minoritized academics in our study felt within their workplaces depended upon their experiences with 1) acceptance (e.g., through hiring, promotion, and tenure); 2) visibility (e.g., in terms of perceived power in informal and formal work interactions); 3) support (e.g., via collegial and administrative encouragement, assistance, collaboration and resource support); and 4) mentoring (e.g., in terms of providing and seeking mentor experiences). Our findings suggest that the increasing presence of racially minoritized academics may better serve institutional purposes of portraying a mission of diversity than actually achieving a mission of equity.